A Reusable, Compliant, Small Volume Blood Reservoir for In Vitro Hemolysis Testing. Issue 2 (18th April 2016) - Olia, Salim E.; Herbertson, Luke H.; Malinauskas, Richard A.; Kameneva, Marina V.
Abstract: Bench‐top in vitro hemolysis testing is a fundamental tool during the design and regulatory safety evaluation of blood‐contacting medical devices. While multiple published experimental protocols exist, descriptions of the test loop reservoir remain ambiguous. A critical fixture within the circuit, there is no readily available blood reservoir that ensures thorough mixing and complete air evacuation: two major factors which can affect results. As part of the Food and Drug Administration (FDA) Critical Path Initiative, we developed a three‐piece reservoir consisting of a 3D‐printed base, a plastic clamp set, and a medical‐grade blood bag. This simple, reusable, and cost‐effective design was used successfully in the hemolysis assessment of FDA benchmark nozzles and prototype rotary blood pumps, and may be useful as an integral component to any in vitro blood circulation loop.